Kill Rate and Evaluation of Ex Vivo PK/PD Integration of Cefquinome Against Actinobacillus pleuropneumoniae - Zhang, Longfei; Xie, Hongbing; Wang, Hongjuan; Ding, Huanzhong; Zhang, Gaiping; Hu, Jianhe (Frontiers in Veterinary Science, 2021)
We wished to study the detailed and precise antibacterial activity of cefquinome against Actinobacillus pleuropneumoniae (APP) in vitro and ex vivo. We analyzed the relationships between kill rate and cefquinome concentration in broth and between pharmacokinetic/pharmacodynamic (PK/PD) parameters and antibacterial effect in serum and tissue cage fluid (TCF) of piglets. Cefquinome exhibited time-dependent antibacterial activity against APP according to the kill rate. The maximum kill rate was 0.48 log10 CFU/mL/h at the 0-9-h period in broth. In the ex vivo PK/PD study, the maximum concentration (Cmax), time to reach the maximum concentration (Tmax), terminal half-life (T1/2β), and area under the concentration time curve (AUCinfinity) were 5.65 μg/ml, 0.58 h, 2.24 h, and 18.48 μg·h/ml in serum and 1.13 μg/ml, 2.60 h, 12.22 h, and 20.83 μg·h/ml in TCF, respectively. The values of area under the curve during 24 h/minimum inhibitory concentration (AUC24h/MIC) for bacteriostatic, bactericidal, and bacterial eradication effects were 18.94, 246.8, and 1013.23 h in serum and 4.20, 65.81, and 391.35 h in TCF, respectively. Our findings will provide a valuable basis for optimization of dosage regimens when applying cefquinome to treat APP infection.